ALOKASI WAKTU, MOTIVASI, KENDALA, DAN NIAT BERWIRAUSAHA PADA ISTERI NELAYAN - Maehara, Derina; Yuliati, Lilik Noor (Jurnal Ilmu Keluarga dan Konsumen, 2013)
This study aimed to analyze the difference of time allocation of fishermen’s wives on common days and harvest; the correlation between allocation of time, motivation, barrier, and entrepreneurial intentions; and also influence of allocation of time, motivation, and barrier toward entrepreneurial intentions of fishermen’s wives. The study involved 100 fishermen’s wives that were selected purposively. Data was collected through interviews. The result showed that time allocation of fishermen’s wives was differ significantly on common days and harvest. Time allocation of productive activity increased on harvest compared to common days. Correlation analysis showed that entrepreneurial motivation correlated negative significantly with barrier and positive significantly with entrepreneurial intentions. Meanwhile, entrepreneurial intentions correlated negative significantly with entrepreneurial barrier. The finding also revealed that the motivations, barriers, and time allocation on productive activities at common days influenced entrepreneurial intentions significantly.